Formation of the public accounting student in the international accounting teaching process: A training proposal - Torres Garay, Alejandro (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2023)
This paper presents an analysis of the training of public accounting students in Colombia in the teaching of international accounting, with the aim of diagnosing and analysing the methodologies applied in the foundation and contextualisation of international financial reporting standards (IFRS). It is a proposal that is elaborated through primary sources (surveys), which were applied to students and graduates. It is hoped that as a result of this work, actions will be generated that promote the development of competencies and skills in relation to IFRS in public accountants.